Learning Styles in ELT - Vachová, Kateřina (Univerzita Pardubice, 2012)
The thesis deals with the issue of learning styles in the processes of English language teaching/learning. The primarily focus of the thesis is on sensory learning styles. Each of the learning styles is discussed in connection with suitable didactic means for the needs of learners with the given dominant style. The need to respect individual learning styles by providing varied learning activities is emphasized. The aim of the practical part is to discover whether teaching is varied in terms of sensory learning styles. The thesis is concluded with proposals for modifications of the teaching processes so that they accommodate all the learning styles.
Styly učení žáků v procesech vyučování
Keywords: žáci; styly učení; vizuální typy; auditivní typy; kinestetické typy; diferenciace; learners; learning styles; visual types; auditory types; kinesthetic types; differentiation